Significance of dermal and respiratory uptake in creosote workers: exposure to polycyclic aromatic hydrocarbons and urinary excretion of 1-hydroxypyrene. Issue 3 (March 1995) - Elovaara, E; Heikkilä, P; Pyy, L; Mutanen, P; Riihimäki, V
Abstract : OBJECTIVES--To evaluate workers' exposure in a creosote impregnation plant by means of ambient and biological monitoring. METHODS--Naphthalene (vapour phase) and 10 large molecular polycyclic aromatic hydrocarbons (PAHs) (particulate phase) were measured in the breathing zone air during an entire working week. 1-Hydroxypyrene (1-HP) was measured in 24 hour urine as a metabolite of the pyrene found in neat (dermal exposure) and airborne creosote. RESULTS--Naphthalene (0.4-4.2 mg/m3) showed 1000 times higher concentrations in air than did the particulate PAHs. In total, the geometric mean (range) of three to six ring PAHs was 4.8 (1.2-13.7) micrograms/m3; pyrene 0.86 (0.23-2.1) micrograms/m3, and benzo(a)pyrene 0.012 (0.01-0.05) micrograms/m3. There was no correlation between pyrene and gaseous naphthalene. The correlations between pyrene and the other nine particulate PAHs were strong, and gave a PAH profile that was similar in all air samples: r = 0.83 (three to six ring PAHs); r = 0.81 (three ring PAHs); r = 0.78 (four to six ring PAHs). Dermal exposure was probably very high in all workers, because the daily output of urinary 1-HP exceeded the daily uptake of inhaled pyrene by < or = 50-fold. Urinary 1-HP concentrations were very high, even on Monday mornings, when they were at their lowest (4-22 mumol/mol creatinine). 1-HP seldom showed any net increase over a workshift (except on Monday) due to its high concentrations (16 to 120 mumol/mol creatinine) in the morning samples. 1-HP was always lower at the end of the shift (19 to 85 mumol/mol creatinine) than in the evening (27 to 122), and the mean (SD) change over the working week (47 (18)) was greater than the change over Monday (35 (32)). The timing of 1-HP sampling is therefore very important. CONCLUSIONS--Urinary 1-HP proved to be a good biomarker of exposure to three to six ring PAHs but not to airborne naphthalene. Hence, biomonitoring based on 1-HP has to be completed with exposure assessment for naphthalene as a marker for creosote volatiles that mainly enter the body through the lungs.